(untitled) (Journal of Intellectual Property and Information Technology Law (JIPIT), 2022)
The core thesis of this study is to explore the legal and technological feasibility to interoperate two mobile health-based solutions in Kenya: Ushauri-Text for Adherence (T4A), and Mobile Laboratory (mLab), to enhance HIV/AIDS care and treatment. This paper focuses on two aspects namely data interoperability by analysing secondary data abstracted from the mLab and the Ushauri databases from June 2017 to June 2018 and doctrinal analysis of the legal and policy environment to support the interoperability. This paper is a case study of the mLab and the Ushauri systems in terms of the technological stack for interoperability which has some legal implications. It includes a pilot study that employed a multistage sampling method in which thirty-nine health facilities in Siaya, Homa bay, Nyeri, and Muranga were selected. Findings show a satisfactory legal environment to augment the interoperability of the two mHealth systems. It is also evident that the two systems were considerably interoperable in terms of technology, semantics, data, and processes. However, interoperating them could largely be compromised by language semantics leading to a discrepancy of characters and numbering in unique identifiers in data entry. Though data in the systems were for the same individuals, it is critical to note that there was a low level of concordance in patient identification numbers in the same facilities where the same patients were receiving clinical services. Additionally, healthcare workers across the various facilities did not follow the NASCOP (2010) eleven-digit unique identifier system. Standardizing human activities while using systems such as the allocation of patient identifiers and following laid down standards while developing systems are critical ways of ensuring interoperability. This paper highlights the need to achieve full-scale implementation of laid down policies and legal requirements such as the systems’ interoperability certification process to standardise the systems and make them interoperable.